Cyber liability insurance in an offender-defender evolutionary game - Fernandez, Ma. Isabel (Animo Repository, 2019)
In a highly inter-connected economy, businesses are under constant threat of being breached by cybercriminals. Traditional security continues to be an integral foundation in addressing risks and threats from a bottom-up perspective. However, security needs to start considering the perspective of cybercrime as a constantly evolving profit-driven economy and the potential of cyber insurance in aligning incentives amongst firms, government and security vendors to improve national security. The adoption of game and decision theory offers a top-down approach that serves as a complement to traditional risk management. With this, we build an evolutionary game to model defending firms and cyber criminals under complete information and bounded rationality with insurance as the focal risk management tool. We find that government intervention is justified in ensuring outcomes parallel with national interests of security, and can support the adoption of cyber insurance.